Pultrusion of Bendable Continuous Fibers Reinforced Composites With Reactive Acrylic Thermoplastic ELIUM® Resin - Zoller, Alexander; Escalé, Pierre; Gérard, Pierre (Frontiers in Materials, 2019)
Continuous fiber reinforced composites were made using in-situ polymerization of a new liquid thermoplastic resin. Depending on the temperature profile in the die and the initiators used, it was shown that PREDICI software enables the simulation of the radical polymerization reaction. By using appropriate sizing of the fibers, the properties of the pultruded part are comparable to standard thermoset resins. Moreover, the specific thermoplastic behavior of the matrix provides to the pultruded part a unique advantage of being post-formable or shapeable as desired while maintaining mechanical performances.